Cultural Concepts in Business Culture - Dolejš, Adam; Ryška, Tomáš, 1976-; Tyll, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
My diploma thesis focuses on the topic of culture within business culture. The main goal of my thesis is to portray cultural concepts from anthropological point of view and introduce a several ways to grasp the concept of culture. Furthermore, the thesis describes the overall phenomenon of business culture as we see them in many studies while pointing out the misconception of business culture which has been repeated since late 70s. In the first part of my thesis, I thoroughly scrutinize the very concept of culture and the ways the concept has been shaped during past century. In the second part of the master thesis, overall grasp of business culture will be described. Finally, I will discuss the terrible misconception of the concept of culture (business culture) within the business studies literature.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses